Vaiko statusas Rytų Lietuvoje geležies amžiuje - Kurila, Laurynas (Archaeologia Lituana, 2007)
The social roles and status of children as well as the views of childhood have been very diverse in past societies. They depend on the society’s mentality, its cultural and economic basis, demographic situation. For the archaeologist, children are of great importance not only as specific social strata, but also as an indicator of social organization. The knowledge of children in the past, though, is still scarce despite of the large volume of investigations. This paper reviews the position of children in the Iron Age Lithuanian tribe. The research is based on mortuary data.The study is built on the results of an osteological analysis of 393 burials (64 inhumations and 329 cremations) from 65 barrow cemeteries. The remains of at least 482 individuals were identified in the burials. The age at death of 475 individuals was determined more or less accurately. The individual remains were divided into 6 age groups, the first four of which fall into the subadult category. The presumable number of individuals was statistically evaluated for each group.The number of newborns and infants under 1 year buried in barrows is surprisingly low (1.9%). The death rate of infants in pre-industrial societies was no less than 20-25%. A small number of infant graves most probably indicates their low status. They could have been buried differently than adults, in different locations, in separate cemeteries or parts of them, or not buried at all. The emotional bonds with infants were probably not as strong as in the modern world. They did not provide the family any economic benefit but were more of a burden until a certain age.In the graves from the early period (4–6th c.) the infants were buried together with adults, mostly women. It is likely that newborns were buried only in the instances of simultaneous death with the mother after childbirth. The graves were fairly richly equipped and contained artefacts manufactured from rare materials (silver, glass, amber). This should reflect the higher status. The cremation infant burials of the 8-11/12th c. were dug into previously created barrows. Only a few grave goods or their remains were found in them. No reasonable answer can be given to the question why in precisely these instances the infants were buried in barrows.A far greater number of children were buried in barrows (the presumable numbers are 8.2% for the 1-5 age group and 12.0% for the 5-12 age group). Similar child mortality has also occurred in other past populations. Children with better immunity used to survive the infancy. At this age they probably received better care. Certain dangers characteristic to infancy (specific illnesses, infanticide) no longer threatened them.From the second or third year of life children were apparently all buried in community cemeteries. This signifies the recognition of the child as a member of the society. The funeral rites of children differ from those of adults and were less time and labour consuming, though. 50.5% of the children were interred in collective graves with older individuals. Perhaps the remains of children were not always immediately buried after cremation. Collective burial was mostly practiced in the 5-7th c. During the 3-7th c. a new barrow was created in burying a child in the majority of the cases while during the 8-11/12th c. most of the children’s graves were dug into earlier mounds.Out of 46 graves of children alone the determination of the gender by the grave goods was possible in 29 cases. The burials of 7 male and 22 female children were identified. The biggest inadequacy appears in the 8-11/12th c. cemeteries. It can be argued that in burying a boy usually no effort was made to stress his male gender.Fairly abundant and diverse grave goods were placed into children’s graves. Some of them were of a rare form, imported, manufactured of gold and silver. The richest children’s burials belong to the 2nd quarter - middle of the 1st millennium. The most expensive artefacts in children’s burials are the female grave goods, while weapons are scarce. The grave goods in collective burials are less diverse and expensive, although far more weapons (dedicated probably to the adults) were placed into them.Far fewer (5.5%) remains of adolescents of the age of 12-20 have been identified. The mortality in this age group was low in many past populations. The status of adolescents expressed through the funeral rites was higher than that of younger individuals. The funeral rites for them were essentially the same as those for adults. Only 27.3 or 31.8% of them were buried in collective burials, and only 33.0% of burials had been dug into earlier barrows. An individual who had reached the age of 12-15 was most likely already recognised as a full member of the society.The assemblages of the grave goods consist mainly of small metal artefacts. None of them was of a rare form or made of precious metals. In burying an adolescent, as a means of expressing status, the symbolic content of the grave goods was probably the key factor. The community did not place many gifts in the grave of an adolescent believing that he or she is already able to take care of himself or herself in the afterlife. However, until the age of maturity (18-22) adolescents are still at a lower social level than adult males, which is expressed through small number of weapons in the graves.A review of children’s funeral rites reveals four dimensions of status: individual age, gender, inherited status, and chronological change. At least three thresholds of a change in a child’s status are distinct as he grows: after surviving the infancy (becoming a part of society), at the beginning of sexual maturity (becoming an independent social persona, hut still having no higher individual position), and full biological and social maturity. Analogous stages of status as well as expression of them in funeral rites are observed in other past societies.The change in status is not uniformly articulate in the burials of both genders. The reflection of the maturity of girls is not so noticeable in funeral rites. Their graves were furnished in the same manner as those of adult females. Sharp distance in status is evident between boys and adult males, though. A boy was not recognised as equal to the adult males. Both sexes of children comprised an almost genderless group of society, a sort of ‘third gender’, which in many respects was closer to the female than the male gender.Many differences are also noticeable among the burials of children of the same age. The vertical gradation of society and inherited status are reflected to a certain extent in children’s funeral rites. The different means of expressing higher status intercorrelate.From a chronological perspective the change in the status of children is possible to envisage. During the entire period the development of funeral rites towards being plainer and less differentiated is noticeable. The children’s burials from the early stage (3/4-5/6th c.) do not significantly differ in their construction and furnishings from the adult burials. The sets of grave goods in 5th c. burials are the most diverse in respect to both quantity and quality. The burial constructions and grave goods of the 7/8-11/12th c. are considerably plainer and in a way more standardised. During this period, status became more dependent on age. This perhaps reflects certain stagnation in social relations, which decreased the society’s stratification and the importance of the inheritance of position.